Lost Utopia in Palestinian Flash Fiction - Saffuri khoury, samah (International Journal of Language and Literary Studies, 2024)
The present study examines the use of dystopia as a device in Palestinian flash fiction composed by writers living in Israel. The study will look at three examples of flash fiction and investigate how dystopia is manifested in the stories’ plot, characters and language, in an attempt to evaluate the relationship between the distorted reality that came into being after the war of 1948 and the social, political and economic effects it left. I therefore examined the themes which Palestinian writers have addressed in flash fiction and investigated their use of dystopia in order to express the state of crisis in which Palestinians inside Israel live, and how this affects the plot, the language and the characters. Our study shows that dystopia has been used in order to express the state of crisis in which individuals live and their inability to accept the psychological and economic damage left by the war, as reflected in the characters, who gradually lose their hope for a secure future.